PETROPHYSICAL EVALUATION WITH MULTIMIN AND XPT VALIDATION OF COORIKIANA SANDSTONE IN A DEPLETED FAULT BLOCK, COOPER BASIN - Yansen Christiano (Universitas Islam Sumatera Utara, 2025)
In glauconitic shaly-sand reservoirs of the Cooper Basin, conventional Archie-based saturation calculations overestimate water saturation by failing to quantify clay-bound water, potentially misdirecting reserve estimates in structurally complex downdip blocks. This study integrates wireline logs with a constrained Multimin petrophysical model explicitly incorporating Illite, Kaolinite, and Glauconite and validates results against 19 XPT pressure/mobility measurements in the Isoptera 2 development well. The analysis quantifies 10.4 m of net oil pay (PHIE 15.2%, Sw 51%), confirming a 6 m structural uplift while extending proven reserves 370 m downdip. Critically, XPT data reveals a 190 psi depletion in the CC35-10 zone, yet retained mobility of 5.13 mD/cP proves commercial hydraulic connectivity persists despite nearby production. This integrated workflow resolves the longstanding underestimation risk in shaly Cooper Basin sands, providing a calibrated standard for reliably de-risking downdip reservoir quality and pressure communication using Multimin constrained by field-specific XPT calibration.